2016
DOI: 10.1002/adfm.201600243
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Controlling the Work Function of Perovskite Oxides Using Density Functional Theory

Abstract: Perovskite oxides containing transition metals are promising materials in a wide range of electronic and electrochemical applications. However, neither their work function values nor an understanding of their work function physics have been established. Here, we predict the work function trends of a series of perovskite (ABO 3 formula) materials using Density Functional Theory, and show that the work functions of (001)-terminated AO-and BO 2 -oriented surfaces can be described using concepts of electronic band… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
120
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 86 publications
13
120
0
Order By: Relevance
“…21,[34][35][36][37] These materials are, in order of their 3d electron count calculated using formal valences: LaScO3, SrTiO3, LaTiO3, SrVO3, LaVO3, LaCrO3, La0.75Sr0.25MnO3 (LSM25), LaMnO3, SrFeO2. 75 15,46 Based on the trends in TM d-band center in Figure 2B, qualitatively, for all functionals, when progressing from low to high 3d electron count, the 3d band tends to shift down in energy, with a higher fraction of the 3d band being filled.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…21,[34][35][36][37] These materials are, in order of their 3d electron count calculated using formal valences: LaScO3, SrTiO3, LaTiO3, SrVO3, LaVO3, LaCrO3, La0.75Sr0.25MnO3 (LSM25), LaMnO3, SrFeO2. 75 15,46 Based on the trends in TM d-band center in Figure 2B, qualitatively, for all functionals, when progressing from low to high 3d electron count, the 3d band tends to shift down in energy, with a higher fraction of the 3d band being filled.…”
Section: Introductionmentioning
confidence: 88%
“…The O p-band center is defined as the centroid of the projected density of states of the oxygen 2p orbitals relative to the Fermi level, as shown schematically in Figure 1, and information regarding the band center calculations can be found in Section 4. Properties predicted using the O p-band center include: vacancy and interstitial formation and migration energies, [11][12][13][14] work functions, 15 and catalytic properties such as the high temperature surface exchange rate for the oxygen reduction reaction (ORR) in solid oxide fuel cells, 11,16,17 binding energies of reaction intermediates for aqueous oxygen reduction and evolution reactions, 18,19 and overpotentials of oxygen evolution reaction (OER) and ORR in basic solution. 17,20 However, discrepancies exist among predictions made using different Density Functional Theory (DFT) exchange and correlation functionals, and from experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was also found that the electronic structures of some perovskite surfaces differ from that in bulk, which is mainly attributed to surface states entering the band gap. [29][30][31][32] This property can lead to the increase in the surface conductivity compared to that in bulk, [33][34][35] 41 and various hydrocarbons 42 without being affected by the harsh operation conditions. Recently, Dai et al took one step forward to utilize a two-dimensional electron gas at LaAlO 3 /SrTiO 3 interface for fast and selective detection of various oxidizing and reducing gases at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and modeling efforts have started to develop formalisms for the defect structure and chemistry of (2D) grain boundaries, surfaces, and interfaces, and have captured surface and grain‐boundary reconstruction in thermodynamic equilibrium situations . Improved understanding of dynamic interfaces, such as oxygen exchanging electrodes or oxide catalysts supporting chemical synthesis, has been gained by operando imaging and spectroscopy and supported by simple models . However, to date it has not been possible to fully model these highly driven systems due to their size, complexity, and intricate boundary conditions.…”
Section: Defect‐enabled Phenomenamentioning
confidence: 99%
“…78 Improved understanding of dynamic interfaces, such as oxygen exchanging electrodes 79,80 or oxide catalysts supporting chemical synthesis, has been gained by operando imaging and spectroscopy 81 and supported by simple models. 82 However, to date it has not been possible to fully model these highly driven systems due to their size, complexity, and intricate boundary conditions. More extended predictive simulation of oxide interfaces under complex drivers and at extended spatial and time scales requires further progress in computing, including both higher performance supercomputers and novel computational methods to extend time scales 83 and spatial scales 84 to the ranges that address interface behavior and its evolution.…”
Section: Challenge #2: the Defect Genomementioning
confidence: 99%